2020
DOI: 10.3390/w12061826
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Children’s Blood Lead Levels from Exposure to Lead in Schools’ Drinking Water—A Case Study in Tennessee, USA

Abstract: Lead (Pb) exposure can delay children’s mental development and cause behavioral disorders and IQ deficits. With children spending a significant portion of their time at schools, it is critical to investigate the lead concentration in schools’ drinking water to prevent children’s exposure. The objectives of this work were to predict students’ geometric mean (GM) blood lead levels (BLLs), the fractions of at-risk students (those with BLLs > 5 μg/dL), and the total number of at-risk students in one Tennessee s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…There is no established method or reference level to define high or low water lead risk building wide. Previous studies have used the average lead level in a building to determine risk, , but average levels could mask the overall risk to children and students in a building from clusters of outlier taps or even single taps. Indeed, extremely high variability from tap to tap should be expected within schools and child care facilities. , The assumption that the average lead level represents actual exposure to children because of equal consumption across all taps within a building, as previously posited, is also not supported by lead exposure assessments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no established method or reference level to define high or low water lead risk building wide. Previous studies have used the average lead level in a building to determine risk, , but average levels could mask the overall risk to children and students in a building from clusters of outlier taps or even single taps. Indeed, extremely high variability from tap to tap should be expected within schools and child care facilities. , The assumption that the average lead level represents actual exposure to children because of equal consumption across all taps within a building, as previously posited, is also not supported by lead exposure assessments.…”
Section: Methodsmentioning
confidence: 99%
“…There is no established method or reference level to define high or low water lead risk building wide. Previous studies have used the average lead level in a building to determine risk, 11,28 but average levels could mask the overall risk to children and students in a building from clusters of outlier taps or even single taps. Indeed, extremely high variability from tap to tap should be expected within schools 6 and child care facilities.…”
Section: Data Set Development the Clean Water For Carolinamentioning
confidence: 99%
“…The Integrated Exposure Uptake Biokinetic (IEUBK) and the Bowers models were employed to evaluate the potential risks of consuming prolonged stagnant tap water by elementary and high school students, respectively. 17,35,36 Since no quantitative models depicting the lead uptake into the bloodstream for students at the middle school age level were available, blood lead level extrapolations have been made only for the elementary and high school students. Although the default values for dietary lead intake (2.22 μg per day), water consumption (0.59 L per day for IEUBK and 2.0 L per day for Bowers), and soil ingestion (0.085 g per day for IEUBK and 0.02 g per day for Bowers) were used, site-specific lead concentrations for soil (52 μg g −1 ), household water (8.63 μg L −1 ), and school water (data from experimental samples) were imported into the model.…”
Section: Methodsmentioning
confidence: 99%
“…As previous authors have suggested, this difference in effects is likely attributed to young children being more susceptible to lead absorption than older populations, given similar environmental conditions. 17,44 However, since both populations were affected, the models indicate that the extended stagnation could potentially have a detrimental effect on all students' health if they drink the water that was stagnant for an extended period. The distribution of increases in at-risk students across all schools is shown in Fig.…”
Section: Blood Lead Level Modelingmentioning
confidence: 99%
See 1 more Smart Citation